A green approach for enhancing oxidation stability including long storage periods of biodiesel via Thuja oreantalis L. as an antioxidant additive. (1st October 2019) - Devi, Anuchaya; Das, Vijay Kumar; Deka, Dhanapati
Graphical abstract: Highlights: New application of Thuja extract as an additive to biodiesel. Waste cooking oil has been used for biodiesel preparation. Enhancement in oxidation stability as well as storage stability of biodiesel. Thuja extract could be a nature based renewable alternative biodiesel additive. Abstract: In this study, we evaluated leaf extract of Thuja oreantalis L. as a natural antioxidant additive for biodiesel oxidation stability enhancement. Primarily the total phenolic content has been tested by Folin ciocalteu method and free radical scavenging capacity has been tested against DPPH (1, 1-diphenyl-2-picryl-hydracyl). Other techniques like HPLC, FT-IR and 1 H NMR analyses have been done for identification of the antioxidant compounds. The Thuja extract is further characterized by powder XRD, SEM, TEM and BET techniques. A total of six concentrations of Thuja extract (TSE) are used for evaluating the antioxidant activity in biodiesel i.e. 0 ppm (TSE0 ), 100 ppm (TSE1 ), 250 pmm (TSE2 ), 500 ppm (TSE3 ), 1000 ppm (TSE4 ) and 2000 ppm (TSE5 ). The results revealed that a minimum concentration of 100 ppm of Thuja extract in the WCB produced from waste cooking oil was capable of enhancing its induction period (IP) from 4.55 h to 6.79 h, which meet both the standard specifications for biodiesel oxidation stability i.e. European (ENE14214) and American (ASTM D-6751). Comparison of oxidation stability enhancement in biodiesel employing TBHQ (tertiary butylhydroquinone) and Thuja extract has been studied along with long storage periods. This study adds one more dimension in the field of exploration of natural antioxidants for biodiesel quality enhancement.